Plant Systematics (Elsevier/Academic Press, 2006)
"Plant Systematics contains the essential paradigms, concepts, and terms required for a basic understanding of plant systematics. The text introduces readers to the morphology, evolution, and classification of land plants by presenting basic information in understandable terminology. Chapters cover systematic methodology, evolution and classification of plants, evidence and descriptive terminology, and resources in plant systematics. They contain numerous color photos of features and specific groups of plants, many of which are of dissected material carefully labelled to show salient features of the plant. Review questions and exercises complement each chapter." "This book is appropriate for researchers, students, and professionals in plant systematics, plant taxonomy/floristics, plant diversity, plant morphology, botany and related disciplines."--Jacket.